Anang, an entrepreneurial engineer, introduces Malaysian-flavoured Shawarma - Amira Wayhida Izzati, Mohamad Amin; Halizan, Mohmood (UMPSA, 2024)
GAMBANG, 22 February 2024 - The increasingly busy lifestyle of Malaysians, prioritizing healthy and fast-food options, has led to the growing popularity of food services.